SPE International Symposium on Oilfield Chemistry 1999
DOI: 10.2118/50731-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structures of Group 4 Metal Crosslinkers for Polygalactomannans

Abstract: This paper was prepared for presentation at the 1999 SPE International Symposium on Oilfield Chemistry held in Houston, Texas, 16-19 February 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Because guar and guar derivatives are known to cross-link with group IV metals, 16 the viscosity of several such gels was tested while changing pressure. As shown in Figures 5 (titanium cross-linker) and Figure 6 (zirconium cross-linker), neither the titanium-nor the zirconium-cross-linked gel showed large responses to pressure.…”
Section: Results and Discusssionmentioning
confidence: 99%
“…Because guar and guar derivatives are known to cross-link with group IV metals, 16 the viscosity of several such gels was tested while changing pressure. As shown in Figures 5 (titanium cross-linker) and Figure 6 (zirconium cross-linker), neither the titanium-nor the zirconium-cross-linked gel showed large responses to pressure.…”
Section: Results and Discusssionmentioning
confidence: 99%
“…Due to the needs of deep/ultra-deep fracturing, researchers have proposed organometallic crosslinking agents. Compared with inorganic crosslinking agents, the intermolecular bond energy between organometallic crosslinking agents and thickeners is large, which can greatly improve the temperature resistance of fracturing fluids [38]. Due to the large specific surface area and abundant active hydroxyl groups of nanomaterials, some scholars have prepared nano-crosslinking agents, which can effectively increase the size of crosslinking agents and crosslinking sites, reduce the dosage of thickeners needed, and reduce fracturing costs [39].…”
Section: Crosslinked Gel Fracturing Fluidsmentioning
confidence: 99%
“…Viscosity A wide usable temperature range for viscosity stability is desired when implementing a new crosslinked fracturing gel. Throughout the development of the res-free fluid, transition metal-based crosslinkers (Harry et al 1999) were found most favorable for providing the necessary fluid stability and crosslink behavior (i.e., instant or delayed mechanism). Results displayed in Fig.…”
Section: Conductivitymentioning
confidence: 99%